2014
DOI: 10.1021/jz5008802
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Reactivity of Nitric Acid with Nascent Sea Spray Aerosol: Large Differences Observed between and within Individual Particles

Abstract: Current climate and atmospheric chemistry models assume that all sea spray particles react as if they are pure NaCl. However, recent studies of sea spray aerosol particles have shown that distinct particle types exist (including sea salt, organic carbon, and biological particles) as well as mixtures of these and, within each particle type, there is a range of single-particle chemical compositions. Because of these differences, individual particles should display a range of reactivities with trace atmospheric g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(114 citation statements)
references
References 39 publications
9
103
0
Order By: Relevance
“…However, few studies have measured PM emitted from oil and gas extraction in the Arctic. Measurements of BC from 1977 to 1997 in Utqiaġvik showed contributions from Russian oil fields year round (Polissar et al, 1999(Polissar et al, , 2001), similar to the recent results of Barrett et al (2015) at Utqiaġvik during December 2012-March 2013 when transported particles from Russian oil fields were observed. Barrett et al (2015) also measured regional Arctic BC from both fossil fuel combustion and biomass burning.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, few studies have measured PM emitted from oil and gas extraction in the Arctic. Measurements of BC from 1977 to 1997 in Utqiaġvik showed contributions from Russian oil fields year round (Polissar et al, 1999(Polissar et al, , 2001), similar to the recent results of Barrett et al (2015) at Utqiaġvik during December 2012-March 2013 when transported particles from Russian oil fields were observed. Barrett et al (2015) also measured regional Arctic BC from both fossil fuel combustion and biomass burning.…”
Section: Introductionsupporting
confidence: 85%
“…Measurements of BC from 1977 to 1997 in Utqiaġvik showed contributions from Russian oil fields year round (Polissar et al, 1999(Polissar et al, , 2001), similar to the recent results of Barrett et al (2015) at Utqiaġvik during December 2012-March 2013 when transported particles from Russian oil fields were observed. Barrett et al (2015) also measured regional Arctic BC from both fossil fuel combustion and biomass burning. The Arctic Climate Change, Economy, and Society (ACCESS) aircraft field campaign recently investigated emissions from oil and gas extraction in the Norwegian Arctic and measured increased BC, among other pollutants, compared to the Arctic background while sampling within plumes from oil and gas extraction facilities (Roiger et al, 2015).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…This can lead to the formation of partially or fully reacted particles containing NaCl and NaNO 3 over a range of mixing ratios. Indeed, studies of individual marine aerosols have clearly shown the existence of fully or partially reacted SSA particles, and a significant portion of these particles were reported to be mixtures of sodium chloride, nitrate, and/or sulfate (Gard et al, 1998;Ro et al, 2001;Laskin et al, 2003;Ault et al, 2014). Moreover, the further reactive uptake of N 2 O 5 was reported to be dependent on the chloride to nitrate ratio of the reacted SSAs and their phases .…”
Section: Gupta Et Al: Hygroscopic Properties Of Nacl and Nano 3 Mmentioning
confidence: 99%
“…The even carbon number preference of C 12 eC 22 is associated with marine bacteria, fungi and yeast species (Grimalt and Albaiges, 1987), and possible petroleumderived inputs, such as petroleum residue (Harji et al, 2008). It has been suggested that marine aerosols could be derived from the bubble bursting upon breaking waves on the ocean surface, which is also known as sea spray (Ault et al, 2014). Sea spray aerosol (SSA) plays a key role in influencing inorganic and organic aerosol burden over much of the Earth's surface (Salter et al, 2014).…”
Section: Concentrations Of Carbonaceous Aerosolsmentioning
confidence: 99%